Non-intubated video-assisted thoracoscopic surgery vs. intubated video-assisted thoracoscopic surgery for thoracic disease: a systematic review and meta-analysis of 1,684 cases - Zhang, Kai; Chen, Hui-Guo; Wu, Wei-Bin; Li, Xiao-Jun; Wu, Yong-Hui; Xu, Jian-Nan; Jia, Yu-Bin; Zhang, Jian (Journal of Thoracic Disease, 2019)
Background: Non-intubated video-assisted thoracoscopic surgery (NIVATS) has been increasingly used in lobectomy, bullectomy, wedge resection, lung volume reduction, sympathectomy and talc pleurodesis, which may reduce postoperative complications. However, the benefits of non-intubated and intubated methods of VATS remain controversial. Methods: We comprehensively searched PubMed, Web of Science, Embase and the Cochrane Library, and performed a systematic review to assess the two techniques. Random and fixed-effects meta-analytical models were used based on the low between-study heterogeneity. Study quality, publication bias, and heterogeneity were assessed. Results: Compared to intubated methods, NIVATS had a lower postoperative complications rate [odds ratio (OR): 0.63; 95% confidence interval (CI), 0.46–0.86; P